Project Success Factors Analysis Business Construction - Suyoso, Aldo Lovely Arief (Manunggal Halim Jaya, 2024)
Project success factors relate to the risk of uncertainty in a job that experiences additions or deletions from the original scope of work according to the contract, thereby changing the entire contract value and even the completion time of the job. This research aims to analyze the influence of soundness of business and workforce, planning and control, and safety performance on the success of construction projects. Using a quantitative explanatory methodology, the research utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS), used in this work via SmartPLS software. A structured survey was used to gather information from 100 contractors in Surabaya. The findings reveal a positive relationship between the soundness of the business and the workforce and planning, control, and safety performance to project success in construction projects.